2008
DOI: 10.1016/j.jrp.2008.07.009
|View full text |Cite
|
Sign up to set email alerts
|

How personalized and socialized power motivation facilitate antisocial and prosocial decision-making

Abstract: ARTICLE INFO ABSTRACTIn two studies. we investigate the effects of individuals' power motivation on decision Keywords: making. We distinguish between two types of power motivation [McClelland. D. C. In separating out the independent effects of each type of power motivation. we are able to explain more variance in decision-making behavior across various contexts than in models using aggregate power motivation (personalized plus socialized). Power motive Motivation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
94
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 50 publications
5
94
0
Order By: Relevance
“…Most previous research suggests that power intensifies dispositional tendencies toward prosocial behavior -allowing the kind to behave even more kindly, and the selfless to pursue unfettered their selfless aims (e.g., Cöté, Kraus, Cheng, Oveis, van der Lowe, Lian, & Keltner, 2011;DeMarree, Briñol, & Petty, 2014;Hirsch, Galinsky, & Zhong, 2011;Hoogervorst, de Cremer, van Dijke, & Mayer, 2012;Magee & Langner, 2008). By contrast, we examine responsibility as a mediator, not as a dispositional moderator.…”
Section: Discussionmentioning
confidence: 96%
“…Most previous research suggests that power intensifies dispositional tendencies toward prosocial behavior -allowing the kind to behave even more kindly, and the selfless to pursue unfettered their selfless aims (e.g., Cöté, Kraus, Cheng, Oveis, van der Lowe, Lian, & Keltner, 2011;DeMarree, Briñol, & Petty, 2014;Hirsch, Galinsky, & Zhong, 2011;Hoogervorst, de Cremer, van Dijke, & Mayer, 2012;Magee & Langner, 2008). By contrast, we examine responsibility as a mediator, not as a dispositional moderator.…”
Section: Discussionmentioning
confidence: 96%
“…The need for power has been associated primarily with assertive, aggressive and reprehensible behaviour and outcomes (Magee & Langner, 2008, p. 1547. Specifically as explained by Fodor, Wick, and Conroy (2012, p. 1), power relates negatively to making concessions during conflict resolution, and to positively assert friendship and risk taking.…”
Section: Leadership Power and Motivationmentioning
confidence: 99%
“…Although power has been studied in a number of ways in the field of social psychol ogy, implicit social cognition research on power has focused on how individuals' social positions and power mindsets might implicitly affect their social behavior. For example, one study showed that different power motivations, socialized versus personalized, led to different outcomes (Magee & Langner, 2008). Specifically, socialized (other serving) power motivations led to more deliberation and more prosocial outcomes, and personalized (self serving) motivations led to less deliberation and more antisocial outcomes (Magee & Langner, 2008).…”
Section: Powermentioning
confidence: 99%
“…For example, one study showed that different power motivations, socialized versus personalized, led to different outcomes (Magee & Langner, 2008). Specifically, socialized (other serving) power motivations led to more deliberation and more prosocial outcomes, and personalized (self serving) motivations led to less deliberation and more antisocial outcomes (Magee & Langner, 2008).…”
Section: Powermentioning
confidence: 99%
See 1 more Smart Citation